Exploring the relationship of employee wellness and job performance among lecturers in UiTM Malacca City Campus / Nur Adilla Abdul Aziz and Nur Soraya Abdullah - Abdul Aziz, Nur Adilla; Abdullah, Nur Soraya (2015)
The purpose of this research is to find out the role of wellness aspect towards job performance among lecturers in UiTM Malacca City Campus. There are four objectives had been set in this study. First, to examine the relationship between weight status and job performance. Second, to examine the relationship between exercise and job performance. Third, to examine the relationship between stress and job performance and forth, to identify the most significant factor that contributes towards job performance. In order to complete this study, the data was obtained from primary data through the distribution of questionnaires. Pertaining to that, 148 lecturers in UiTM Malacca City Campus were chosen as respondent for this study. Only 108 responses were returned back to the researchers. Then, all the collected data were analyzed by using Statistical Package for Social Science (SPSS). From the correlation testing, the result shows two independent variables which are weight status and stress have no significant relationship with job performance while exercise has a significant relationship towards job performance. Moreover, the result also revealed that exercise is the only one factor that influence job performance. Besides that, the hypotheses testing displays that only exercise factor is accepted, while the other two hypotheses concerning weight status and stress are rejected. In conclusions, it shows that individuals who adopt exercise practice as their part of wellness lifestyle will ultimately increase the job performance.